2016
DOI: 10.1371/journal.pntd.0004257
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Determined MBL Deficiency Is Associated with Protection against Chronic Cardiomyopathy in Chagas Disease

Abstract: Chagas disease (CD) is caused by Trypanosoma cruzi, whose sugar moieties are recognized by mannan binding lectin (MBL), a soluble pattern-recognition molecule that activates the lectin pathway of complement. MBL levels and protein activity are affected by polymorphisms in the MBL2 gene. We sequenced the MBL2 promoter and exon 1 in 196 chronic CD patients and 202 controls. The MBL2*C allele, which causes MBL deficiency, was associated with protection against CD (P = 0.007, OR = 0.32). Compared with controls, ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 59 publications
0
23
0
1
Order By: Relevance
“…Similarly, MBL genotypes with low expression were also correlated with increased pathology (59). However, a recent study found that low-MBL genotypes were associated with reduced pathology in Chagas' disease patients (60). Thus, variation in MBL levels can impact both early and late events during both acute and chronic Chagas' disease.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, MBL genotypes with low expression were also correlated with increased pathology (59). However, a recent study found that low-MBL genotypes were associated with reduced pathology in Chagas' disease patients (60). Thus, variation in MBL levels can impact both early and late events during both acute and chronic Chagas' disease.…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributed in part to the genetic aspects and immune competence of local human populations (Ayo et al, 2013; Deng et al, 2013; Frade et al, 2013; Luz et al, 2016; Nogueira et al, 2012) and/or to parasite genetic heterogeneities. The latter hypothesis finds support in animal studies (that do not strictly recapitulate Chagas disease-associated physiopathologies), which revealed inter-strain variations in complex phenotypes such as parasitemia, virulence, tissue tropism/distribution and pathogenicity (Figure 1) (Andrade et al, 1999; Andrade, 1990; Camandaroba, Pinheiro Lima and Andrade, 2002; de Souza et al, 1996; Laurent et al, 1997; Monteiro et al, 2013; Revollo et al, 1998; Roellig et al, 2010).…”
Section: Trypanosoma Cruzi An 'All-wheel Drive' Parasitementioning
confidence: 99%
“…The current consensus states that a failure to down-regulate the inflammatory response, which is maintained by parasite persistence in tissues, appears to play a predominant role. Other contributory factors include sex, age and genotypic features of the patient, route of infection, sustained vector exposure, auto-immune responses and the existence of co-infections (Ayo et al, 2013; Bonney and Engman, 2015; Deng et al, 2013; Frade et al, 2013; Luz et al, 2016; Machado et al, 2012; Nogueira et al, 2012; Tarleton, 2015; Teixeira et al, 2011). As mentioned, a possible role of parasite genotype on Chagas disease progression/outcome has been proposed, though further research supported by novel and robust epidemiologic and diagnostic tools, and appropriate animal models are needed to address this issue.…”
Section: Diagnostic Applications For Chagas D Isease: Present Knowledgementioning
confidence: 99%
“…Different studies have demonstrated the crucial role of complement as a first line of defence against T. cruzi infection, as well as in the maintenance of chronic infection and severity of CCC . The complement system includes more than 35 plasma proteins/regulators and cell surface receptors which act together in the recognition and elimination of microbial and foreign cells.…”
Section: Introductionmentioning
confidence: 99%
“…in the maintenance of chronic infection 11 and severity of CCC. [12][13][14][15] The complement system includes more than 35 plasma proteins/regulators and cell surface receptors which act together in the recognition and elimination of microbial and foreign cells. In order to keep complement activation under homeostatic conditions, an effective and fine system of regulatory molecules, such as complement Factor H (FH), is required.…”
mentioning
confidence: 99%